SIPN South: six years of coordinated seasonal Antarctic sea ice predictions - Massonnet, François; Barreira, Sandra; Barthélemy, Antoine; Bilbao, Roberto; Blanchard-Wrigglesworth, Edward; Blockley, Ed; Bromwich, David H.; Bushuk, Mitchell; Dong, Xiaoran; Goessling, Helge F.; Hobbs, Will; Iovino, Doroteaciro; et al. (Frontiers in Marine Science, 2023)
See document.